Maternal and fetal complications from COVID-19; a comparative analysis - Shamsher, Saadia; Amin, Said (Khyber Journal of Medical Sciences, 2022)
Background The pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has exposed vulnerable populations of pregnant ladies to an unprecedented global health crisis. The data from previous human coronavirus pandemics suggest that pregnant women and their fetuses are particularly susceptible, leading to poor outcomes. The objective of this study was to summarize the clinical manifestations and maternal and perinatal outcomes during pregnancy in pandemic COVID-19 and compare them with non-pandemic in 2019. Material and Methods A total of 2169 pregnant women in the third trimester of their pregnancies who delivered in our hospital from May 2020 to August 2020 were selected as observation group (during pandemic COVID-19), while 1812 pregnant ladies who gave birth from May 2019 to Aug 2019 as a control group (during non-pandemic). A comparative analysis of the two groups was performed with the chi-square test, and P-value was calculated for significance between the two groups. Results The difference in the overall rate of maternal complications and fetal outcome was not statistically significant. The maternal complications post-term pregnancy and preterm delivery (P<0.05) are significantly more in the observed group than in the control group. Furthermore, we found that among fetal outcome birth asphyxia was significantly more in the observed group than the control group. Conclusion: In the COVID-19 pandemic and the antenatal care provision, this comparative analysis of maternal and fetal complications shows an excellent management plan despite robust applications of pandemic SOPS, as there is no significant difference in both groups.